Deficiency of WFS1 increases vulnerability to pathological tau in vitro and in vivo: Molecular and cell biology/tau. (7th December 2020) - Chen, Shuo; Venkaraman, Lalitha; Liang, Jiawen; Nakano, Yoshi; Villegas, Nancy E. Hernandez; Brown, Cris; Urano, Fumihiko; Koks, Sulev; Serrano, Geidy E.; Beach, Thomas G.; Davies, Peter; Diamond, Marc; et al.
Abstract: Background: Pathological tau accumulates in patients with Alzheimer's disease (AD) and related tauopathies. However, it remains unclear why specific neuronal subtypes and brain regions are vulnerable to pathological tau in early AD. Recently we found excitatory neurons expressing the Wolframin (WFS1) in the entorhinal cortex and the CA1 of hippocampus are particularly vulnerable to pathological tau in tau transgenic mice and human AD. However, the role of WFS1 in mediating this selective neuronal vulnerability is unknown. Method: The tau aggregates in live cells were imaged as individual tiles and stitched via the Zeiss Observer 7 fluorescent microscope, and then the area with tau aggregates in each stitched image was quantitated by Image J. The tau pathology in mouse brain was visualized by MC1‐positive and conformation‐dependent tau via the immunofluroscent staining. The protein interaction between WFS1 and tau was measured by the Duolink Proximity ligation assay (PLA) and co‐immunoprecipitation (CO‐IP) assay. Result: Here we reported that overexpression of human WFS1 significantly reduced DS9 tau seeding in SH‐SY5Y cells stably transfected with P301S mutant tau, while overexpression of mutant P724L WFS1 did not. Also, overexpression of human WFS1 significantly reduced exogenous tau aggregation in primary mouse mixed neurons treated with P301S tau‐YFP lentivirus, while overexpression of mutant WFS1 did not. Furthermore, the heterozygotes of PS19 tau;Nestin Cre/+ ; Wfs1 f/+ brain‐specific knock‐out mice and PS19 tau;Wfs1 +/‐ knock‐out mice have much more tau pathology in the Dentate gyrus, CA1 and entorhinal cortex compared with PS19 tau and PS19 tau;Wfs1 f/+ mice. The homozygotes of PS19 tau;Nestin Cre/+ ;Wfs1 f/f brain‐specific knock‐out mice and PS19 tau;Wfs1 ‐/‐ knock‐out mice have even more tau pathology than those heterozygotes. We further identified that WFS1 interacts with both total tau and pathological tau in primary cultured neurons, wild‐type and tau transgenic mice, and human non‐AD and AD cases. The interaction is first enhanced as tau pathology increases, however, it is reduced as tau pathology further increases. Conclusion: Taken together, we demonstrate that deficiency of Wfs1 increases vulnerability to pathological tau in vitro and in vivo, indicating WFS1 may be a therapeutic target for preventing or delaying the tau pathology in AD.